Facile synthesis of porous Nb2O5 microspheres as anodes for lithium-ion batteries. (2nd March 2017) - Liu, Guangyin; Jin, Bo; Bao, Keyan; Xie, Haiquan; Guo, Jiali; Ji, Xiaoguang; Zhang, Ruixue; Jiang, Qing
Abstract: Porous Nb2 O5 microspheres have been prepared by a facile solvothermal method and subsequent heat-treatment using cheap NbCl5 as a starting material. As anode materials for lithium-ion batteries (LIBs), porous Nb2 O5 microspheres show good electrochemical performance with discharge capacities of 199 mA h g −1 after 50 cycles at a current density of 100 mA g −1 and 126 mA h g −1 after 150 cycles at a current density of 500 mA g −1, respectively. The good electrochemical performance of porous Nb2 O5 microspheres can be ascribed to the distinct structure of the microspheres consisted of nanoparticles with short transport route for ion and electron, large specific surface and mesoporous structure. The electrochemical testing results demonstrate that porous Nb2 O5 microspheres are the promising alternate as anode materials for LIBs. Highlights: Porous Nb2 O5 microspheres have been prepared by a facile solvothermal method and subsequent heat-treatment. Porous Nb2 O5 microspheres possess mesoporous structure. Porous Nb2 O5 microspheres show high capacity and excellent cycling stability.